Gangguan Berbahasa pada Anak Autis Ringan : Studi Kasus Anak Usia 13 Tahun - Annisa Aulia Rahma; Akifah Humaira Salsabila (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language disorders mean obstacles, obstacles, and something that causes a person's inability to pronounce articulation sounds, or words to express, say, and convey thoughts, ideas, and feelings. This study aims to describe language disorders in mild autistic children aged 13 years. This research was conducted using a descriptive qualitative method. The data in this study are the results of a 13-year-old conversation with a subject with mild autistic disorder with the initials